Commercial Graphite Flakes as an Adsorbent of Janus Green Dye from Aqueous Solution: Adsorption Kinetics and Isotherms Study - Abood, Nagham H.; H. Merza, Sundus (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Commercial graphite (CGT) powder was used as an adsorbent surface for cationic dye, Janus green (JG), from aqueous solutions. This study aims to highlight the practical significance of using inexpensive CGT as an efficient adsorbent for the removal of JG dye from industrial wastewater. CGT was characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction. The adsorption process was investigated by examining parameters like the weight of the adsorbent, contact time, and temperature. Pseudo-second-order kinetic (PSO), pseudo-first-order, and intraparticle diffusion were used for analyzing the kinetic data. JG dye’s adsorption kinetics fit the PSO kinetic model well (R2= 0.999). Furthermore, the thermodynamic functions such as entropy (ΔS*), enthalpy (ΔH*), and Gibbs free energy (ΔG*) were evaluated. The positive value of (ΔH*) confirms that the adsorption process is endothermic. Also, the positive value of ΔS* suggests an increase in randomness at the solid-liquid interface during dye adsorption, and non-spontaneous as evidenced by positive ΔG* values of 76.686, 76.130, 75.574, and 75.018 kJ/mol at different temperatures. Two segment-linear plots have been used to describe the intraparticle diffusion analysis of JG adsorption onto CGT, and the plot does not meet the origin point, indicating that the intraparticle diffusion was not the only controlling step. Based on the calculated value of ΔH*= 92.701 kJ/mol, which means that the adsorption is a chemical type. Langmuir, Freundlich, and Temkin isotherms were studied for their isothermal behavior. Also, the equilibrium state is attained in 45 minutes. At 318.15 K, the maximum removal percentage of JG achieved is 99.96%, indicating that the graphite surface is suitable as an adsorbent surface for removing JG dye in the temperature range studied